Sedimentary evidence of glacial lake outburst floods (GLOFs) during the last glacial maximum in the Venetian-Friulian plain (NE Italy). (10th February 2020) - Monegato, G.; Mozzi, P.; Paiero, G.; Rossato, S.
Abstract: The outwash rivers of the Venetian-Friulian plain promoted a high-rate aggradation during the Last Glacial Maximum (LGM), with large sedimentary bodies fed by major glaciers along the south-eastern side of the Alps. Glaciers were temperate-type, hold up by high precipitation rates and characterized by large amount of water trapped in subglacial lakes or funneled in speedy streams. The stratigraphic analysis of these sedimentary bodies showed sharp changes from coarse gravels to well-sorted sandy gravels few kilometers downstream. Large boulders, 1–2 m in size, are present in many sites, especially in the Tagliamento outwash plain, from the end-moraine system to about 13 km far to the south. Most of the boulders are located on the eastern area of the sandur and lie stratigraphically above a paleosol, radiocarbon dated to 31, 114 ± 643 cal a BP, thus belonging to the LGM sandur of the Tagliamento glacier. In some locations these boulders are associated to large bars, showing a rough cross-bedding. Similar sedimentary structures are observed 2 km downstream of the LGM frontal moraines in the Astico outwash system, a 25-km-long transfluence tongue of the Adige-Brenta glacial complex. In this case the occurrence gravel dunes containing many boulders marks the evidence of a high-energy deposition. The occurrence of cross-bedded bars, embedding large boulders up to 2 m of diameter, in the piedmont plain of the south-eastern Alps is peculiar. Breaks of natural dams, such as the frontal moraines or the glacier itself, may have triggered glacial lake outburst floods (GLOFs) that determined the formation of such gravel bars with meter-size clasts.